Is there any place for the variable angle proximal femoral plate? A case matched cohort study against the Dynamic Hip Screw system. Issue 10 (October 2016) - Tucker, A.; Diamond, O.; McDonald, S.; Johnston, A.; Neil, M.; Kealey, D.; Archbold, P.
Abstract: Introduction: The Variable angle Martin Plate (MP) is designed to offer patient-specific adaption for the treatment of intertrochanteric hip fractures. Its proposed benefits include optimization of lag screw placement, plate shaft congruence and reduced risk of failure. Often its use has been criticized as representing a poor reduction of the fracture. The purpose of this study was to assess for a poorer quality of reduction, and compare functional outcomes and mortality, using a MP to that of a fixed angle Dynamic Hip Screw (DHS) in a matched cohort of patients. Methods: A retrospective review of a prospective fracture database system was undertaken between 1st January 2004 to 31st December 2013. MP patients were matched to a cohort of DHS patients. Outcomes measure were a quality of procedure score(QPS), 1-year mortality rates, reoperation rates, and Barthel Index functional outcome. Minimum follow up was 12 months. Results: A total of 77 Martin Plate patients were identified and case matched. The mean pre- and post-op Neck Shaft Angle (NSA) in the MPs was significantly different (132.97 ± 7.78 Vs 126 ± 8.62; p < 0.0001). Conversely, the mean pre op DHS NSA and the mean post op NSA was not (p = 0.397). Mean Tip-Apex Distance (TAD) was significantly different between groups; MP mean 26.51 ± 9.09 mm vs DHS 23.50 ± 8.14 mm (p = 0.023). The QPS consisted of 4 variables. A significant inverse relationship between QPS and the incidence of construct related complications exists. TAD > 25 mm, and a change in AP NSA of >5°conveyed the greatest risk of complications. No difference occurred in complications, nor 12-month mortality. Conclusions: No statistical difference was found in the quality of reduction between MP and DHS in this group of matched patients. QPS demonstrated a significant inverse correlation with implant-related complications. No significant difference was noted in the incidence of complications, Barthel Index functional scores, or 12-month mortality between implants. A rationale exists regarding the use of MPs, particularly in patients with varus NSA. However, planning and adequate reduction are essential regardless of implant choice.